FENOMENOLOGI APLIKASI TIKTOK BAGI USAHA ONLINE MARICA FARMS - Asia Khairunnisa Luthan; Zahira Xenia Asmoro Putri (Kinesik, 2021)
The TikTok phenomenon has become a widespread phenomenon throughout the world. The TikTok application is now a trend as well as evidence of technological developments that help humans carry out their activities. Not only as a medium for self-existence but also used by online business actors, one of which is Marica Farms. This study aims to describe the phenomenology of the TikTok application for Marica Farms' online business. Marica Farms is an online animal sacrifice business that uses the TikTok application to help market its products. Using a phenomenological approach, the researcher finds out the meaning of the TikTok application for Marica Farms' online business. Equipped with Uses and Gratification Theory which helps researchers in analyzing the phenomenon of the TikTok application for Marica Farms online business. Data were collected using in-depth interviews with the owners of Marica Farms. The results of this study are the phenomenology of the TikTok application for Marica Farms' online business, namely as a medium that makes it easier for online businesses to have things out of the box, reach a broad market and help increase knowledge and awareness of Marica Farms' online business. The content provided by TikTok Marica Farms has also been adapted to the needs of its audience, such as information and entertainment needs so that the audience feels satisfied.